Magnetoelectric Dipole Antenna with Dual Polarization and High Isolation. (11th April 2018) - Yang, Xujun; Ge, Lei; Zhang, Dengguo; Sim, Chow-Yen-Desmond
Abstract : A dual-polarized aperture-coupled magnetoelectric (ME) dipole antenna is presented in this paper. The feeding network is based on substrate-integrated coaxial lines (SICLs). To describe the effect of the SICL on improving the isolation, the ME dipole with another two different feeding configurations, microstrip lines and striplines, respectively, is compared. As such, the coupling between the transmission lines is tremendously reduced and the isolation between the two input ports of different polarization is enhanced. An antenna prototype is fabricated and tested, exhibiting good performances, including an isolation level of higher than 30 dB between the two input ports and gains of more than 9.5 dBi. Besides, the proposed design is capable of achieving stable directional radiation patterns with cross-polarization levels lower than −22 dB and back radiation levels lower than −24 dB.